2017
DOI: 10.1080/13607863.2017.1370689
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimers’ disease and caregiving: a meta-analytic review comparing the mental health of primary carers to controls

Abstract: Caregivers of patients with AD experience poor mental health in comparison to the general population, with female caregivers being disproportionately affected. Further exploration of the psychosocial variables that contribute to these group differences is needed to inform effective support services and, in turn, help caregivers manage the emotional demands of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 110 publications
2
70
0
2
Order By: Relevance
“…Of those providing care to someone with dementia for more than 5 years, 63% are women 324 . Similarly, caregivers who are women may experience slightly higher levels of burden, impaired mood, depression and impaired health than men, with evidence suggesting that these differences arise because female caregivers tend to spend more time caregiving, assume more caregiving tasks, and care for someone with more cognitive, functional and/or behavioral problems 329,330 . Of dementia caregivers who indicate a need for individual counseling or respite care, the large majority are women (individual counseling, 85%, and respite care, 84%) 324…”
Section: Caregivingmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those providing care to someone with dementia for more than 5 years, 63% are women 324 . Similarly, caregivers who are women may experience slightly higher levels of burden, impaired mood, depression and impaired health than men, with evidence suggesting that these differences arise because female caregivers tend to spend more time caregiving, assume more caregiving tasks, and care for someone with more cognitive, functional and/or behavioral problems 329,330 . Of dementia caregivers who indicate a need for individual counseling or respite care, the large majority are women (individual counseling, 85%, and respite care, 84%) 324…”
Section: Caregivingmentioning
confidence: 99%
“…• A meta-analysis reported that caregivers of people with dementia were significantly more likely to experience depression and anxiety than non-caregivers. 330 Approximately 30% to 40% of family caregivers of people with dementia report depression, compared with 5% to 17% of non-caregivers of similar ages. [358][359][360][361][362] • The prevalence of depression is higher among dementia caregivers (30% to 40%) than other caregivers, such as those who provide help to individuals with schizophrenia (20%) or stroke (19%).…”
Section: Caregiver Emotional and Social Well-beingmentioning
confidence: 99%
“…The population of individuals with dementia in the United States is expected to almost triple by 2060 [1], which will lead to a significant increase in the number of caregivers. Therefore, it is imperative to identify ways to improve caregivers' quality of life and well‐being, as caring for individuals with dementia often leads to detriments in caregivers' physical and mental health, which can also indirectly impact the patient's well‐being [4–7,12,13]. The present study investigated a novel 2‐day intervention in decreasing symptoms of depression, anxiety, burden, and perceived stress in family caregivers of individuals with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Stage of dementia was assessed with the Functional Assessment Staging Tool (FAST) [16]. The FAST scale consists of seven major functional levels (1)(2)(3)(4)(5)(6)(7), which are concordant with the corresponding global level of functional capacity and cognition of the Global Deterioration Scale, with a higher number corresponding to greater impairment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation